A survey of consumer expectation in community pharmacies in Bandung, Indonesia - Nasrul Wathoni and Susi Afrianti Rahayu (Journal of Applied Pharmaceutical Science, 2014)
The pharmacy has an important social as well as a functional role within an integrated health care system. Service quality has been an important topic to both health care providers and marketers as well as the focus of much recent research. This study was aimed to measure the service quality of community pharmacy based on patient’s perceptions. A written survey was carried out among pharmacy costumers (n=500) in Bandung, Indonesia (in 5 community pharmacies). The survey method used questionnaire with Cross-Sectional descriptive study approaches and SERVQUAL model. The level of patient satisfaction was mapped by Cartesian diagram. Mapping attribute on Cartesian Diagram majority on quadrat B, means the patients who purchased the prescription was satisfied with the services provided. The results showed that patients who purchased their prescription at five of community pharmacies overall very satisfied with the services provided and no one really needs to be a priority to increase the satisfaction of patients with prescription treatments given.
Keywords: Community pharmacy, patient, satisfaction, prescription, service.